2020
DOI: 10.3390/microorganisms8091343
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity and Antibiotic Susceptibility of Sparus aurata from Aquaculture

Abstract: In a world where the population continues to increase and the volume of fishing catches stagnates or even falls, the aquaculture sector has great growth potential. This study aimed to contribute to the depth of knowledge of the diversity of bacterial species found in Sparus aurata collected from a fish farm and to understand which profiles of diminished susceptibility to antibiotics would be found in these bacteria that might be disseminated in the environment. One hundred thirty-six bacterial strains were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 112 publications
0
30
0
Order By: Relevance
“…strains resulted in resistance to ertapenem and meropenem, antibiotics used in serious clinical infections. Several antibiotics for which resistance was found in these isolates appear in the World Health Organization list of “critically important antimicrobials” and “highly important antimicrobials” for human medicine [ 126 ]. In Mediterranean aquaculture, and in particular the Greek fish farm facilities, several registered antibiotics are currently available against bacterial infections, including tetracyclines, quinolones, and fluoroquinolones, potential sulfa, penicillin, and chloramphenicol derivatives.…”
Section: Antibiotic Resistance In the Mediterranean Basinmentioning
confidence: 99%
“…strains resulted in resistance to ertapenem and meropenem, antibiotics used in serious clinical infections. Several antibiotics for which resistance was found in these isolates appear in the World Health Organization list of “critically important antimicrobials” and “highly important antimicrobials” for human medicine [ 126 ]. In Mediterranean aquaculture, and in particular the Greek fish farm facilities, several registered antibiotics are currently available against bacterial infections, including tetracyclines, quinolones, and fluoroquinolones, potential sulfa, penicillin, and chloramphenicol derivatives.…”
Section: Antibiotic Resistance In the Mediterranean Basinmentioning
confidence: 99%
“…Information about the frequency and pathogenicity of other genera found in this study in bivalve mollusks is scarce. However, there are several studies reporting human infections caused by all seven genera described above, namely wound infections, foodborne diseases (by ingestion of raw seafood), myonecrosis, septicemia, necrotizing fasciitis, empyema, bacteremia, endocarditis, severe respiratory, urinary and biliary tract infections, meningitis, and keratitis [ 9 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genera Enterobacter , Enterococcus , Klebsiella , Proteus , Providencia, and Staphylococcus , as well as the species from Citrobacter freundii complex, Escherichia coli , Morganella morganii , Shewanella algae and Vagococcus fluvialis , found in this study, were already reported in bivalve mollusks (especially clams, mussels and oysters) [ 12 , 13 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. These groups of bacteria, some of which are fish pathogens, are commonly found in aquatic environments [ 12 , 25 , 34 , 35 , 37 , 38 ]. All these bacteria were already associated with human infections, such as ear and eye infections, osteomyelitis, infective arthritis, endocarditis, bacteremia, meningitis, intestinal and urinary tract infections, brain abscess, peritonitis, enteritis and septicemia, and some are recognized as important agents in nosocomial infections [ 12 , 13 , 34 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations